Student Group Work Participation Barriers in Tanzania Higher Learning Institutions: Understanding Major Barriers - Kinyaduka, Bryson Daudi (Journal of Education and Practice, 2025)
Purpose: The paper intended to establish major barriers impeding effective student participation in group work. It was important to understand the major barriers in order for higher learning institutions to use, or find plausible solutions for the same. Methodology: The study used exploratory sequential design. Phase I of qualitative data collection used a sample of 24 student participants, and phase II which involved the collection of quantitative data used a sample size of 357 student respondents. Thus, the sample size was 381 subjects in total. In phase I, the study used Focus Group Discussion to collect data. In phase II, the study used questionnaire to collection data. The sampling techniques used in phase I was Maximum Variation sampling technique, and in phase II convenience sampling technique was adopted. Findings: The major barriers for student effective group work participation include: inadequate preparation before group work discussion meetings; difficulty in handling some of personalities; poor time management; and assignment lumping. Unique Contribution to Theory, Practice and Policy: The paper informs about major barriers impeding effective student participation in group works. The study is an eye opener to policy and by-law makers in higher learning institutions in Tanzania and elsewhere it applies. It discerns barriers needing attention in policies and by-laws. Importantly, it informs about where to focus to help students successfully learn through group work teaching strategy for the same to make it effective.